Seaweeds of the Greek coasts : Rhodophyta excluding Ceramiales - Tsiamis, Konstantinos (Array, 2019)
An updated checklist of the red seaweeds (Rhodophyta), excluding the order Ceramiales, of the Greek coasts is provided, based on literature records, critically reviewed from present-day taxonomic and nomenclatural aspects. The total number of genera, species and infraspecific taxa currently accepted is 78, 138 and 4 respectively. The occurrence of each taxon in the North Aegean, South Aegean and Ionian Seas is given. Knowledge gaps are pointed, with 57 taxa pending confirmation of their presence marked. Moreover, 13 excludenda and 12 inquirenda taxa are briefly discussed. In overall, a solid updated baseline of the Rhodophyta (excluding Ceramiales) taxa occurence in Greece is provided, critical for future tailor-targeting seaweed studies.